2022
DOI: 10.1063/5.0075283
|View full text |Cite
|
Sign up to set email alerts
|

Coordination polymers for emerging molecular devices

Abstract: Conductive coordination polymers are hybrid materials with the potential to be implemented in the next generation of electronic devices, owing to several desirable properties. A decade ago, only a few scattered examples exhibiting conductivity existed within this class of materials, yet today groups of coordination polymers possess electrical conductivities and mobilities that rival those of inorganic semiconductors. Many currently emerging energy harvesting and storage technologies are limited by the use of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 156 publications
0
17
0
Order By: Relevance
“…Coordination polymers (CPs), as a class of crystalline solids consisting of metal nodes and organic linkers, are at the forefront of materials science as they offer enormous application potential in electronics 1 , magnetics 2 , and optics 3 . However, their single crystals, constructed by directional coordination bonds, are intrinsically brittle, which severely limits their utility in applications such as flexible electronics and smart wearable devices 4 , 5 . It has been recently demonstrated that bendable organic crystals could be applied as deformable optical waveguides and circuits 6 , flexible conductors 7 , and ferroelectrics 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Coordination polymers (CPs), as a class of crystalline solids consisting of metal nodes and organic linkers, are at the forefront of materials science as they offer enormous application potential in electronics 1 , magnetics 2 , and optics 3 . However, their single crystals, constructed by directional coordination bonds, are intrinsically brittle, which severely limits their utility in applications such as flexible electronics and smart wearable devices 4 , 5 . It has been recently demonstrated that bendable organic crystals could be applied as deformable optical waveguides and circuits 6 , flexible conductors 7 , and ferroelectrics 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The conductivity was determined by preforming a current–voltage sweep using a four-point contact method to a film, deposited from solution via drop casting on an interdigitated finger pattern. The detailed approach, in addition to the operational principles of the interdigitated finger pattern, is provided in the Supporting Information and in Morritt et al 27 The current–voltage sweeps for Ni–Cu and Cu–Cu are shown in full in Figure S4 of the Supporting Information. The Cu–Cu data shows a clear linear pattern with a degree of hysteresis, with the value of conductivity calculated as approximately 2.5 × 10 –8 S cm –1 .…”
Section: Conductivitymentioning
confidence: 99%
“…All of these factors are known to influence the resulting material properties. [39][40][41][42][43] The small size of the formate ion, however, prevents the formation of solvent accessible void spaces, reducing the complexity of the structure and properties associated with host-guest interactions. As such, compounds that utilize formate linkers represent the simplest type of a 3-D framework and may serve as a baseline model to interpret periodic trends and properties such as spectroscopic signatures.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the number of possible coordination modes, MOFs and coordination polymers experience significant differences in framework structure, void spacing, and metal–ligand bond strength. All of these factors are known to influence the resulting material properties [39–43] . The small size of the formate ion, however, prevents the formation of solvent accessible void spaces, reducing the complexity of the structure and properties associated with host‐guest interactions.…”
Section: Introductionmentioning
confidence: 99%